Clinicopathological characteristics and clinical outcomes of remnant gastric cancer with endoscopic submucosal dissection - Chen, Xiang-Yu; Wang, Jing; Li, Zi-Yu; Wu, Qi (Frontiers in Oncology, 2025)
BackgroundRemnant gastric cancer is distinct from primary gastric cancer clinically and pathologically. Recently, endoscopic submucosal dissection, widely used for treating early gastric cancer, has also been used to treat remnant gastric cancer. However, owing to the previous surgeries, endoscopic resection of remnant gastric cancer is more complicated. This study aimed to elucidate the clinicopathological characteristics of remnant gastric cancer and evaluate clinical outcomes of endoscopic submucosal dissection for this condition.MethodsThis retrospective study examined the clinicopathological characteristics and clinical outcomes in 30 patients (32 lesions) with remnant gastric cancer who underwent endoscopic submucosal dissection from 2012 to 2023 at the Endoscopy Center of Peking University Cancer Hospital, China.ResultsThe primary disease was a malignant tumor in 25 patients and a benign tumor in 4. Billroth II was the major reconstruction method used in the initial surgery. The median interval from previous surgery to remnant gastric cancer detection was 4.2 years. The mean endoscopic submucosal dissection time was 136 ± 71 min. The en bloc, R0, and curative resection rates were 96.9%, 78.1%, and 71.9%, respectively. While one patient had a perforation during the procedure, none experienced delayed postoperative bleeding. Two patients had local recurrence, and five died during the follow-up. The 5-year overall survival rate was 83.0%.ConclusionsRemnant gastric cancer development is influenced by the type of initial disease and prior surgery. Endoscopic submucosal dissection is a safe and effective treatment for early remnant gastric cancer, with potential applicability for certain non-early-stage lesions. However, being technically challenging, endoscopic submucosal dissection requires the skills of experienced endoscopists and careful evaluation.